Vulnerability analysis based on drought and vegetation dynamics. (October 2019) - Niu, Jun; Kang, Shaozhong; Zhang, Xiaotao; Fu, Jing
Highlights: A vulnerability analysis for vegetation cover in an inland river basin is developed. The severe drought events over the basin are identified for the period 2001–2010. Time-lags of irrigated and non-irrigated vegetation to soil water are quantified. The proposed approach serves to assess regional eco-environmental vulnerability. Abstract: Evaluating the relationship between the vegetation conditions on both non-irrigated (rain-fed) and irrigated lands with the soil water availability at a river basin scale is particularly important, as they address the breadth of vulnerability sources and concentrate on a dominant water factor which reflects the physical processes. A four-step framework is proposed to study the vegetation responses to natural soil water content. Three severe drought events for an inland river basin, the Heihe River basin in Northwest China, are identified for the period of 2001–2010. The severe events occurred within the period from June to September and often lasted about 1–2 months. The time-lags of irrigated and non-irrigated vegetation cover to soil water evolutions are found respectively, ranging from approximately −80 to +80 days, which are associated with regional eco-environmental vulnerability. The negative lags, indicating water deficit for crops, mostly occurred in the eastern part of midstream of Heihe River with farmland. The positive lags mainly appeared at the western part of headwater regions of Heihe River. The efforts to assess the vulnerability of regional vegetation to drought in the context of climate change offer guidance to natural environment and agricultural managements in allocating available water particularly under drought situations.